THE FUTURE DEVELOPMENT OF ACCOUNTING THEORY. - Dein, Raymond C. (The Accounting Review, 1958)
Abstract Accounting is a technology that has developed very recently. With accounting, as with any technology in the process of development, there has been of necessity a good deal of uncertainty as to the best way to do things, and indeed what are the precise things that accounting can be expected to do. The practitioners of a developing technology must continually be on the lookout to devise new and better ways to handle situations already faced and to be ingenious enough to contrive acceptable solutions to new and trying sets of circumstances. The paper takes the position that accounting principles and procedures and standards have developed to the degree that now "an orderly array of interrelated ideas and interconnected reasons" must be attempted if accounting is to realize its full potentialities in serving the business and social ends of which it is capable and which is also its obligation. One characteristic of the U.S. accounting has been that it has been very slow in developing the philosophy that accounting must assert itself as being independent of management. The article gives attention to the conditions under which accounting has developed in the U.S. and how these conditions have contributed to the lack of assertiveness and have influenced considerably what are considered to be the functions of accounting.